Fabrication of highly-specific SERS substrates by co-precipitation of functional nanomaterials during the self-sedimentation of silver nanowires into a nanoporous film. Issue 7 (8th December 2014) - Liu, Rui; Sun, Jie-fang; Cao, Dong; Zhang, Li-qiang; Liu, Jing-fu; Jiang, Gui-bin
Abstract : In this report, we propose and demonstrate the fabrication of a highly-specific SERS substrate by co-precipitating of functional materials, such as nanosorbents and nanocatalysts, into Ag nanoporous films. Abstract : In this report, we propose and demonstrate the fabrication of a highly-specific SERS substrate, which was achieved by the co-precipitation of functional materials, such as nanosorbents and nanocatalysts, into Ag nanoporous films. Based on the nanostructures developed, we performed the ultrasensitive detection of arsenic ions by SERS and monitored the catalyzed reactions using real-time SERS.